2021
DOI: 10.1128/aem.00947-20
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification, Active Uptake, and Intracellular Accumulation of Chromium Species by a Methane-Oxidizing Bacterium

Abstract: Despite the wide-ranging proscription of hexavalent chromium, chromium (VI) remains among the major polluting heavy metals worldwide. Aerobic methane-oxidizing bacteria are widespread environmental microorganisms that can perform diverse reactions using methane as the feedstock. The methanotroph Methylococcus capsulatus Bath, like many other microorganisms, detoxifies chromium (VI) by reduction to chromium (III). Here, the interaction of chromium species with M. capsulatus Bath was examined in detail by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…These results confirmed that strain M2 could accumulate Cr(III) through intracellular localization. Our study is in line with the previous reports demonstrated using Methylococcus capsulatus [57], Escherichia coli K-12 [58], Sinorhizobium sp. [48], and Bacillus sp.…”
Section: Ftir Raman Spectroscopy and Tem-edx Analysis On The Rhizobac...supporting
confidence: 94%
“…These results confirmed that strain M2 could accumulate Cr(III) through intracellular localization. Our study is in line with the previous reports demonstrated using Methylococcus capsulatus [57], Escherichia coli K-12 [58], Sinorhizobium sp. [48], and Bacillus sp.…”
Section: Ftir Raman Spectroscopy and Tem-edx Analysis On The Rhizobac...supporting
confidence: 94%
“…aeMO is carried out by several bacterial lineages belonging to Proteobacteria and Verrucomicrobia. , These methanotrophs routinely possess an oxygen-dependent methane monooxygenase (MMO) to catalyze the conversion of methane to methanol. , Despite the more favorable thermodynamics for oxygen reduction, aeMO can indeed support reduction of many other electron acceptors under hypoxic conditions, such as nitrate, chromate, and ferric iron, which were observed in either axenic cultures or microbial communities. These observations, along with the comparable thermodynamic favorableness, suggest that aeMO could also be potentially coupled to arsenate reduction (aeMO-AsR).…”
Section: Introductionmentioning
confidence: 99%